Delineation of potential groundwater recharge zones using analytical hierarchy process (AHP) - Tanveer Dar (Taylor & Francis Group, 2021)
In the present study, an effort was made in Kashmir Valley, NW-Himalayas to delineate potential groundwater areas using GIS and Analytical Hierarchy method (AHP) by incorporating remote sensing data with data from other sources. These data sets were used to prepare eight thematic layers of slope, soil texture, drainage density, land/land cover (LULC), lithology, geomorphology, lineament density, and rainfall. The analytical method of AHP pair wise matrix was used to evaluate the normalized weight of these thematic layers. All the thematic layers and their corresponding classes were allocated ranks and weights based on their impact on groundwater potential. The study area has been classified into five different potential groundwater recharge zones — excellent (28.97%), good (19.99%), moderate (21.70%), poor (27.16%) and very poor (2.15%). The groundwater potential map prepared for the study area has been validated with 245 existing bore-wells and flow direction of basin. The validation of results was in agreement with the evidence obtained as Area Under Curve (AUC) was calculated to be 79.69% and flow computational investigations which suggest groundwater flows north-eastward from south of basin up to central Kashmir, and south-westward from North towards Jhelum River. The validation suggests that the applied method proves to give us a very significant and reliable result for the study area.